2017
DOI: 10.1111/1467-9817.12131
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of character reading and spelling: A longitudinal study in Chinese

Abstract: Background The aim of this longitudinal study was to examine the relationship between character reading and spelling and to explore the role of reading‐related skills in Chinese literacy. Methods A test battery that included measures of morphological awareness (homophone awareness and compound word awareness), orthographic awareness, rapid automatised naming, character reading, spelling, and IQ was administered to 127 first grade students from two primary schools in mainland China. Results Controlling for IQ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
0
16
1
Order By: Relevance
“…Therefore, reading may play a more important role in the development of morphological awareness. Previous study [ 25 ] has also found that reading affects the development of children’s morphological awareness. The development of morphological awareness could be more affected by reading than by spelling.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, reading may play a more important role in the development of morphological awareness. Previous study [ 25 ] has also found that reading affects the development of children’s morphological awareness. The development of morphological awareness could be more affected by reading than by spelling.…”
Section: Discussionmentioning
confidence: 97%
“…Spelling. The character dictation task was adopted to test spelling including one practice and 36 test items, which had been used in the previous study [25]. Children were asked to write down the target character on an answer sheet (A4 paper size) after it had been repeated three times.…”
Section: Plos Onementioning
confidence: 99%
“…Regarding Chinese character dictation tasks (Li et al, 2017), easyitems and difficult-items dictation tasks were used to examine spelling accuracy. Children were asked to dictate a target word in disyllabic words, such as "读" /du2/ [read] in "读 书" /du2 shu1/ [read books].…”
Section: Spelling Accuracymentioning
confidence: 99%
“…Moreover, spelling is a complex cognitive process that emphasizes accuracy. Spelling accuracy is a core indicator of children's spelling abilities, and dictation has been conventionally adopted to test spelling accuracy in alphabetic languages (Lam and McBride, 2018) and morphosyllabic languages (Li et al, 2017)]. In the process of dictation, when children hear a spoken word, they need to spell out this word, with the help of grapheme-phoneme correspondence and complex orthographic rules (Brown and Ellis, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wong (2018) measured writing fluency using a character copying task with restricted time. In the research of Li et al (2019) , writing was assessed with a dictation task.…”
Section: Introductionmentioning
confidence: 99%